Targeting the Metabolic Reprogramming That Controls Epithelial-to-Mesenchymal Transition in Aggressive Tumors - Morandi, Andrea; Taddei, Maria Letizia; Chiarugi, Paola; Giannoni, Elisa (Frontiers in Oncology, 2017)
The epithelial-to-mesenchymal transition (EMT) process allows the trans-differentiation of a cell with epithelial features into a cell with mesenchymal characteristics. This process has been reported to be a key priming event for tumor development and therefore EMT activation is now considered an established trait of malignancy. The transcriptional and epigenetic reprogramming that governs EMT has been extensively characterized and reviewed in the last decade. However, increasing evidence demonstrates a correlation between metabolic reprogramming and EMT execution. The aim of the current review is to gather the recent findings that illustrate this correlation to help deciphering whether metabolic changes are causative or just a bystander effect of EMT activation. The review is divided accordingly to the catabolic and anabolic pathways that characterize carbohydrate, aminoacid and lipid metabolism. Moreover, at the end of each part we have discussed a series of potential metabolic targets involved in EMT promotion and execution for which drugs are either available or that could be further investigated for therapeutic intervention.